ANALISIS FAKTOR MINAT BELAJAR SISWA PADA PEMBELAJARAN AKUNTANSI DI KELAS XI IPS SMA - Jepri, Yakobus; Okianna, Okianna; Achmadi, Achmadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe purpose of this study was to determine the factors that influence student learning interest in class XII IPS SMA Negeri 1 Terentang District Terentang Kubu Raya Regency. The method used is descriptive research method with the form of a study of the relationship with a sample of 30 respondents from 60 populations. Data collection techniques used are Direct Communication Techniques and Documentary Study Techniques. Based on the results of each indicator. 1). The feelings of students in teaching and learning activities are quite fun although a little boring this is shown by 10 students expressing feelings of pleasure and a little bored. 2). Student interest in learning, from the results of research data showed 18 students expressed useful in learning economics, 15 students expressed interest in the way teachers teach in class and 21 students stated the methods used by teachers were not very varied. 3). Student attention in learning is seen from the accounting material taught so far in accordance with the curriculum or syllabus that has been available from schools, also in accordance with the recommended teacher handbooks. 4). 15 students always do homework assignments given by the teacher, although sometimes they are not completely done by themselves and some do not do assignments.Â Keywords: Accounting Learning, Analysis, Learning Interest